2012
DOI: 10.1016/j.ccr.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

NKX2-1/TITF1/TTF-1-Induced ROR1 Is Required to Sustain EGFR Survival Signaling in Lung Adenocarcinoma

Abstract: We and others previously identified NKX2-1, also known as TITF1 and TTF-1, as a lineage-survival oncogene in lung adenocarcinomas. Here we show that NKX2-1 induces the expression of the receptor tyrosine kinase-like orphan receptor 1 (ROR1), which in turn sustains a favorable balance between prosurvival PI3K-AKT and pro-apoptotic p38 signaling, in part through ROR1 kinase-dependent c-Src activation, as well as kinase activity-independent sustainment of the EGFR-ERBB3 association, ERBB3 phosphorylation, and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
263
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(287 citation statements)
references
References 47 publications
(65 reference statements)
15
263
2
Order By: Relevance
“…Our study also sought to understand how integrin b1 promotes Akt phosphorylation and the acquisition of drug resistance. Of the potentially relevant molecules, Src is known to be a downstream regulator of EGFR and/or integrins and it plays an essential role in the survival of lung cancer cells (35,36). Src is also responsible for the acquisition of resistance to EGFR-targeted drugs (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also sought to understand how integrin b1 promotes Akt phosphorylation and the acquisition of drug resistance. Of the potentially relevant molecules, Src is known to be a downstream regulator of EGFR and/or integrins and it plays an essential role in the survival of lung cancer cells (35,36). Src is also responsible for the acquisition of resistance to EGFR-targeted drugs (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The potential oncogenic role of NKX2-1 in the pathogenesis of adenocarcinoma of the lung was proposed by findings that a region of 14q13.3 containing NKX2-1, NKX2-8, and PAX9 was amplified in approximately 10% of human lung adenocarcinoma (5)(6)(7). Loss-offunction and gain-of-function studies in human lung carcinoma and transformed cells supported a role of NKX2-1 as an oncogene (5)(6)(7)(8)(9); however, the Kras LSL-G12D/+ ;p53 -/-mouse model and a xenograft mouse model supported the concept that NKX2-1 is an antimetastatic factor (10,11).…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, ROR2 also can repress transcription of Wnt target genes and modulate Wnt signaling by sequestering canonical Wnt ligands, thereby serving as a tumor suppressor in different cell contexts (27,28). Although studies have shown that ROR1 or ROR2 can associate with other proteins to modify canonical Wnt signaling or induce noncanonical signaling (29,30), ROR1 and ROR2 are each considered to function independently of one another. We examined primary CLL cells for ROR1-associated proteins and made the unexpected discovery that ROR1 formed heterooligomers with ROR2 in response to Wnt5a to recruit guanine exchange factors (GEFs) that activate Rho GTPases, which can enhance leukemiacell chemotaxis and proliferation.…”
Section: Introductionmentioning
confidence: 99%